2002
DOI: 10.2337/diabetes.51.12.3384
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Insulin in Human Brain Glucose Metabolism

Abstract: The effect of basal insulin on global and regional brain glucose uptake and metabolism in humans was studied using 18-fluorodeoxyglucose and positron emission tomography (FDG-PET). Eight healthy male volunteers aged 49.3 +/- 5.1 years were studied twice in random order. On each occasion, they received an infusion of 0.1 mg. kg(-1). min(-1) somatostatin to suppress endogenous insulin production. In one study 0.3 mU. kg(-1). min(-1) insulin was infused to replace basal circulating insulin levels, and in the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
4
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(165 citation statements)
references
References 49 publications
5
154
4
2
Order By: Relevance
“…Insulin crosses the blood-brain barrier via the saturable transport system (19). Some studies in subjects with normal glucose tolerance have failed to show any effect of insulin on brain glucose metabolism (20), whereas other studies have demonstrated that insulin increases CMR glu (21). However, in our study, the rise in plasma insulin and glucose concentrations after EX was reduced compared with PLC, making this an unlikely explanation for the increase in CMR glu .…”
Section: Discussioncontrasting
confidence: 53%
“…Insulin crosses the blood-brain barrier via the saturable transport system (19). Some studies in subjects with normal glucose tolerance have failed to show any effect of insulin on brain glucose metabolism (20), whereas other studies have demonstrated that insulin increases CMR glu (21). However, in our study, the rise in plasma insulin and glucose concentrations after EX was reduced compared with PLC, making this an unlikely explanation for the increase in CMR glu .…”
Section: Discussioncontrasting
confidence: 53%
“…27 The slow onset of memory enhancement by intranasal insulin in the absence of acute effects speaks for the involvement of gradual plastic neuronal changes. Enhancement of neuronal glucose utilization by insulin 29 as well as the observed suppression of cortisol release may have further supported memory improvement. 30 Glucocorticoids can inhibit synaptic long-term potentiation and decrease hippocampal glutamate turnover by binding to hippocampal glucocorticoid receptors.…”
Section: Discussionmentioning
confidence: 90%
“…More recently, it has been demonstrated that the related IGF-1 is required for brain glucose metabolism in mice (29). In humans it has been demonstrated that insulin acutely regulates brain glucose metabolism during euglycemic hyperinsulinemic clamp studies (30), and by using labeled 2-deoxyglucose we have found decreased glucose uptake in brains of NIRKO mice during a euglycemic hyperinsulinemic clamp (S. Fisher, J.C.B., and C.R.K., unpublished data). In the present study, steady-state brain glucose metabolism under basal conditions, as assessed by PET imaging in NIRKO mice in vivo, was normal.…”
Section: Resultsmentioning
confidence: 99%